2017
DOI: 10.1021/acsnano.7b03569
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Silicon Quantum Dots Enabled High-Sensitivity Ultrabroadband Photodetection of Graphene-Based Hybrid Phototransistors

Abstract: Highly sensitive photodetection even approaching the single-photon level is critical to many important applications. Graphene-based hybrid phototransistors are particularly promising for high-sensitivity photodetection because they have high photoconductive gain due to the high mobility of graphene. Given their remarkable optoelectronic properties and solution-based processing, colloidal quantum dots (QDs) have been preferentially used to fabricate graphene-based hybrid phototransistors. However, the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
293
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(298 citation statements)
references
References 58 publications
2
293
1
2
Order By: Relevance
“…And the authors found that ferroelectric‐driven transistor is capable of detecting the NIR wavelength range 900–1550 nm (Figure d), which due to the depletion of dark current and the change of MoS 2 bandgap caused by the external local electrostatic field from the ferroelectric polymer . Recently, surface plasmon resonance (SPR) technology has been widely used in IR detectors due to its unique properties in resonance absorption, subwavelength confinements, and near‐field enhancements . Wang et al have reported the SPR enhanced NIR photodetector using bilayer MoS 2 and asymmetric Au plasmonic structure consisting of nonresonant wires (NRWs) and resonant wires (RWs) .…”
Section: Individual 2d Metal Chalcogenides For Ir Photodetectionmentioning
confidence: 99%
“…And the authors found that ferroelectric‐driven transistor is capable of detecting the NIR wavelength range 900–1550 nm (Figure d), which due to the depletion of dark current and the change of MoS 2 bandgap caused by the external local electrostatic field from the ferroelectric polymer . Recently, surface plasmon resonance (SPR) technology has been widely used in IR detectors due to its unique properties in resonance absorption, subwavelength confinements, and near‐field enhancements . Wang et al have reported the SPR enhanced NIR photodetector using bilayer MoS 2 and asymmetric Au plasmonic structure consisting of nonresonant wires (NRWs) and resonant wires (RWs) .…”
Section: Individual 2d Metal Chalcogenides For Ir Photodetectionmentioning
confidence: 99%
“…By designing the substrate and components of SPR QDs (quantum dots) artificially, the detectable wavelength was tuned by varying the region for the localized surface plasmon resonance (LSPR) and light absorption band Ni et al dispersed B‐doped Si QDs on the surface of graphene for photodetectors with QDs as the sensitizer. This novel structure obtained good IR light absorption properties with sensitive wavelength spanned from the UV (375 nm) to MIR (3.9 μm) regions (the responsivity and noise equivalent power (NEP) are shown in Figure B).…”
Section: Two‐dimensional Heterostructuresmentioning
confidence: 99%
“…B, Two different optical phenomenon under different radiation and charge transfer between graphene and B‐doped Si QDs, responsivity, and NEP from 375 nm to 3.9 μm. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Two‐dimensional Heterostructuresmentioning
confidence: 99%
“…Copyright 2015, Macmillan Publishers Limited. G, The structure schematic of graphene/Bi 2 Te 3 photodetector . H, The responsivity as the function of incident power .…”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%